Pengaruh Jiwa Kewirausahaan dan Pencatatan Akuntansi pada UMKM Desa Lubuk Nagodang Kecamatan Siulak Kabupaten Kerinci (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to determine the influence of entrepreneurial spirit and accounting records on UMKM in Lubuk Nagodang Village, Siulak District, Kerinci Regency. The dependent variable in this study is UMKM and the independent variables in this study are entrepreneurial spirit and accounting records. This study was conducted using a saturated sampling technique. Data collection techniques used primary data from 35 UMKM. Data were obtained from a questionnaire survey that had been sent to respondents previously using Multiple Linear Regression using SPSS 25. The results of the study indicate that entrepreneurial spirit and accounting records have a significant effect on UMKM in Lubuk Nagodang Village, Siulak District, Kerinci Regency.